Health outcomes and economic burden of hospitalized COVID-19 patients in the United States. (1st January 2021) - Di Fusco, Manuela; Shea, Kimberly M.; Lin, Jay; Nguyen, Jennifer L.; Angulo, Frederick J.; Benigno, Michael; Malhotra, Deepa; Emir, Birol; Sung, Anita H.; Hammond, Jennifer L.; Stoychev, Sophia; Charos, Apostolos
Abstract: Objective: The aims of this study were to evaluate health outcomes and the economic burden of hospitalized COVID-19 patients in the United States. Methods: Hospitalized patients with a primary or secondary discharge diagnosis code for COVID-19 (ICD-10 code U07.1) from 1 April to 31 October 2020 were identified in the Premier Healthcare COVID-19 Database. Patient demographics, hospitalization characteristics, and concomitant medical conditions were assessed. Hospital length of stay (LOS), in-hospital mortality, hospital charges, and hospital costs were evaluated overall and stratified by age groups, insurance types, and 4 COVID-19 disease progression states based on intensive care unit (ICU) and invasive mechanical ventilation (IMV) usage. Results: Of the 173, 942 hospitalized COVID-19 patients, the median age was 63 years, 51.0% were male, and 48.5% were covered by Medicare. The most prevalent concomitant medical conditions were cardiovascular disease (73.5%), hypertension (64.8%), diabetes (40.7%), obesity (27.0%), and chronic kidney disease (24.2%). Approximately one-fifth (21.9%) of the hospitalized COVID-19 patients were admitted to the ICU and 16.9% received IMV; most patients (73.6%) did not require ICU admission or IMV, and 12.4% required both. The median hospital LOS was 5 days, in-hospital mortality was 13.6%, median hospital charges were 43, 986, and median hospital costs were 12, 046. Hospital LOS and in-hospital mortality increased with ICU and/or IMV usage and age; hospital charges and costs increased with ICU and/or IMV usage. Patients with both ICU and IMV usage had the longest median hospital LOS (15 days), highest in-hospital mortality (53.8%), and highest hospital charges (198, 394) and hospital costs (54, 402). Limitations: This retrospective administrative database analysis relied on coding accuracy and a subset of admissions with validated/reconciled hospital costs. Conclusions: This study summarizes the severe health outcomes and substantial hospital costs of hospitalized COVID-19 patients in the US. The findings support the urgent need for rapid implementation of effective interventions, including safe and efficacious vaccines.